Body weight and its effect on other morphometric characters in White Leghorn pullets l33 - Grandía G., Raiden (2016)
The aim of this study was to determine the effect of body weight on other morphometric characters in White Leghorn pullets L33. The study lasted for 6 weeks using 300 pullets (11-16 weeks old) equally distributed in two experimental groups: I: expected body weight (865.6 ± 13.3 g); II: overweighed (920.1 ± 37.3 g). Body weight, tarsus length and distances between pubic bones and from keel to pubis were determined weekly. The Mann-Whitney U test (p<0.05) was used to compare means between groups. Degree of uniformity in body weight in both groups was considered excellent (2.6 and 4.8% for group I and II, respectively). Significant difference between groups was observed in the tarsus length and distance from keel to pubis (p<0.0001), but not on the distance between pubic bones. Also, positive correlation between body weight and other morphometric variables was observed, although only 25.2% of the tarsus length was determined by body weight. It is concluded that body weight has a direct effect on tarsus length in White Leghorn pullets L33, which is potentiated in overweight birds.